2021
DOI: 10.3390/cancers13194869
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of LDE225 in Combination with Gemcitabine and Nab-Paclitaxel in Patients with Metastatic Pancreatic Cancer

Abstract: Background: Desmoplasia is a central feature of the tumor microenvironment in pancreatic ductal adenocarcinoma (PDAC). LDE225 is a pharmacological Hedgehog signaling pathway inhibitor and is thought to specifically target tumor stroma. We investigated the combined use of LDE225 and chemotherapy to treat PDAC patients. Methods: This was a multi-center, phase I/II study for patients with metastatic PDAC establishing the maximum tolerated dose of LDE225 co-administered with gemcitabine and nab-paclitaxel (phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The median OS was 6 months. Moreover, six treatment-related grade 4 adverse events (AEs) and three grade 5 AEs were observed in phase 2 [ 332 ]. Moreover, CXCR2 signaling was found to be involved in iCAF formation and CAF to myCAF conversion.…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…The median OS was 6 months. Moreover, six treatment-related grade 4 adverse events (AEs) and three grade 5 AEs were observed in phase 2 [ 332 ]. Moreover, CXCR2 signaling was found to be involved in iCAF formation and CAF to myCAF conversion.…”
Section: Background Knowledge Of Cafsmentioning
confidence: 99%
“…Consequently, it has led to the introduction of therapies intended to normalize intra-tumoral pressure, vascularization, and drug delivery [43]. Indeed, therapy trials with stroma targeting agents have shown improved perfusion, monitored non-invasively by contrast enhanced ultrasound [4,42] and DCE-MRI [18] in mPDAC as well as in hPDAC [30]. Subsequent reduced vascular collapse and increased drug delivery lead to prolonged survival of the treated animals [4,5,18,42].…”
Section: Discussionmentioning
confidence: 99%
“…For DCE-MRI, commonly used parameters are the volume transfer constant (K trans ) and the extravascular extracellular volume fraction (v e ) determined using Tofts pharmacokinetic modeling [28]. Differences in tumor perfusion and permeability, measured by K trans , were also correlated with biological variations in tissue composition, response to therapy and clinical outcome in PDAC [29][30][31][32]. However, such modeling introduces a high level of complexity and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…As the second SMO antagonist, sonidegib was approved in 2015 for the treatment of advanced basal cell carcinoma. Subsequent studies including clinical trials are in progress to expand its application to other types of cancer [18,19,33]. Apart from its role in cancer therapies, sonidegib was shown to exhibit protective effects in several animal models of CNS disorders, such as AD and ischemic stroke, by inhibiting Aβ-induced memory deficits, neuroinflammation, and glutamate toxicity [22,34].…”
Section: Discussionmentioning
confidence: 99%